Investigating the Financial Crisis of the Iranian Stock Exchange Using Transfer Entropy Method and comparing it with the Dow Jones Financial Market - Mohaghegh, Arefeh (2021)
The focus of the present study is on the financial markets of Iran. In fact, the purpose of the present study is to examine the critical state of the Iranian stock market and compare it with one of the famous American markets called Dow Jones. The purpose of the financial crisis is to examine the effect of the interaction of companies within a market. According to modern financial theory, crisis is a phenomenon of market orientation and finding a negative preferred direction among companies. The stock market data of 180 companies of this market that were active during the period of 2008 to 2019 were used to investigate the financial crisis of the Iranian Stock Exchange. The results show that the average transfer entropy for 180 firms in the Iranian stock market is more random. That is to say, the observed declines do not correspond to the time periods of the crisis in the stock market. Although transfer entropy seems to be a good indicator for determining the period of crisis in the US Dow Jones market, it cannot be an indicator for determining the financial crisis for the Iranian stock market.